ANALISIS EKONOMI HUKUM PIDANA PADA UU PERIKANAN DI INDONESIA - , FUAT WAHYU PRABOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to analyze the Indonesian Supreme Court (Mahkamah Agung) decisions and prosecution to the defendants of IUU Fishing. The data are based on the Supreme Court decisions for IUU Fishing cases, uploaded at putusan.mahkamahagung.or.id. Logistic regression and Tobinâs regression (Tobit) are used in this research to estimate the probability and the intensity of various disposals. This is inline with Becker (1968) argument that the optimal deterrence effect of a disposal arose from the probability of conviction and the intensity of punishment. The results from logistic regression analyses show that the nationality and type of offense is used by the Supreme Court judges to consider the sentences of offender. The results from Tobit regressions show that the intensity of imprisonment is affected by nationality and type of offense. In the other hand, intensity of fines is affected by social cost and nationality.